Detection of volatile organic compounds (VOCs) using an optical fibre long period grating with a calixarene anchored mesoporous thin film - Korposh, Sergiy; Davis, Frank; James, Stephen W.; Wang, T.; Lee, Seung-Woo; Higson, Seamus P. J.; Tatam, Ralph P. (SPIE - International Society for Optics and Photonics, 2013)
A long period grating (LPG) modified with a mesoporous film infused with a functional compound, calix[4]arene, was employed for the detection of volatile organic compounds (VOCs). The mesoporous film consisted of an inorganic part, of SiO2 nanoparticles (NPs) along with an organic moiety of poly(allylamine hydrochloride) polycation PAH, which was finally infused with functional compound, p-sulphanatocalix[4]arene (CA[4]). The LPG sensor was designed to operate at the phase matching turning point to provide the highest sensitivity. The sensing mechanism is based on the measurement of the refractive index (RI) change induced by the complexion of the VOCs with calix[4]arene (CA). The LPG modified with 5 cycles of (SiO2 NPs/PAH)5PAA responded to exposure to chloroform and benzene vapours. The sensitivity to humidity as an interfering parameter was also investigated.
Keywords: Long period grating (LPG); Volatile organic compounds (VOCs); Phase matching turning point (PMTP); Mesoporous film; Layer-by-layer (LbL); calix[4]arene (CA[f])